A technique for selecting potato (Solanum tuberosum) genotypes with low nitrogen requirement - GOVINDAKRISHNAN, P M; SHARMA, R C; KHAN, I A; SHARMA, H C (The Indian Journal of Agricultural Sciences, 2013)
The technique consists of fitting the quadratic model to find relationship between yield of a genotype and N rates,followed by determination ofN dose for getting maximum yields of each genotype including the standard cultivar. Themaximum yield of standard cultivar is termed as fixed yield target. The dose of N for achieving the fixed yield target bya genotype is determined and genotypes requiring less N than standard cultivar are designated as low-nitrogen requiringgenotypes. Methods were also developed to determine the relative and absolute ecofriendly indices of N of the genotypescompared to standard cultivars. Based on the technique, 'P1 376' ('Kufri Ashoka') was identified as low-N requiringearly duration potato (Solanum tuberosum L.) genotype from the tuber yield data of the field experiments conducted atModipuram from 1991-92 to 1993-94. It required 65 kg N/ha compared to 194 kg N/ha for 'Kufri Chandramukhi'(standard cultivar) for attaining a fixed tuber yield target of 33.4 tonnes/ha. In the medium duration 'MS 78-46'tequired 133 kg N/ha compared to 211 kg N/ha by 'Kufri Bahar' (standard cultivar) for attaining yield target of 41.7tonnes/ha. The 'MS 78-46' and 'Kufri Ashoka' were more ecofriendly as their relative and absolute ecofriendly indiceswere higher than the standard cultivars. 'Kufri Ashoka' was more efficient in utillizing N from soil while 'MS 78-46'was more efficient in utillizing N from soil as well as fertilizer source than the standard cultivars.